Ecosystem Services of Living Shorelines: SL494/SS707, 5/2022 - Smyth, Ashley R.; Reynolds, Laura K.; Barry, Savanna C.; Stephens, Natalie C.; Patterson, Joshua T.; Camp, Edward V. (EDIS, 2022)
The purpose of this new 6-page document is to explain the types of ecosystem services provided by different types of living shorelines and how to quantify these values. The target audience for this document is local governments and municipalities that make decisions about developing, conserving, and restoring living shorelines; state management agencies that oversee broader scale habitat management; and finally, homeowners who will be immediately affected by any of these decisions. Written by Ashley R. Smyth, Laura K. Reynolds, Savanna C. Barry, Natalie C. Stephens, Joshua T. Patterson, and Edward V. Camp and published by the UF/IFAS Department of Soil, Water, and Ecosystem Sciences. https://edis.ifas.ufl.edu/SS707